RELATIONSHIP BETWEEN WORKLOAD, WORK-LIFE BALANCE AND WORK PRODUCTIVITY PATI REGENCY EDUCATION AND TRAINING PERSONNEL BOARD EMPLOYEES - Nazula Fajriati (International Conference on Social and Islamic Studies, 2021)
This study aims to determine and analyze the relationship between workload and work-life balance with employee work productivity, at the Education and Training Personnel Board of Pati Regency. This study used a quantitative approach with thepopulation in this study were 40 employees of the Pati Regency Education and Training Personnel Board. The data collection was carried out by distributing questionnaires with a Likert scale, interviews, and documentation studies. The data analysis method used in this study is the variability and reliability test, as well as the Pearson Product Moment correlation test. The results showed that simultaneously the variables of Workload and Work-life Balance did not have a significant relationship with Employee Work Productivity.